Barriers and factors associated with the use of helmets by Motorcyclists: A scoping review. (June 2022) - Mohammadi, Esmaeil; Azadnajafabad, Sina; Keykhaei, Mohammad; Shakiba, Ali; Ebrahimi Meimand, Sepideh; Hosseini Shabanan, Sedighe; Mahdavi Sharif, Pouya; Asgardoon, Mohammad Hossein; Shafieian, Mehdi; Ghodsi, Zahra; Heydari, Seyed Taghi; Atlasi, Rasha; et al.
Highlights: The use of helmets is the main preventive factors of traumatic brain injury among motorcyclists. Demographic and legislative factors play significant role in tendency of motorcyclists to wear helmets. Helmet discomforting characteristics are among the factors of helmet non-usage. Risky behaviors such as drunk driving, demographic factors were also found to be detrimental. Location and time of the ride were among other associates of helmet non-use. Abstract: Road Traffic Injuries (RTIs) have imposed a great global burden on public health. Motorcyclists and pedestrians comprise the most significant proportion of this burden. Several studies have demonstrated a link between helmet wearing and a decline in the impact of RTIs in motorcyclists. In this study, we aimed to review the barriers to helmet utilization by motorcyclists. This scoping review has been conducted in accordance with the guidelines for the systematic review of observational studies and the PRISMA Checklist. The search was conducted by using related keywords in EMBASE, PubMed, Scopus, and Cochrane Library. Four independent reviewers carried out the screening. The main outcomes of interest were barriers to helmet usage among motorcyclists, drawn from the finally included studies. Fifty-three records were selected for data extraction. According to these reports, the barriers and factors associated with helmet usage among motorcyclists were categorized into five entities as: legislations/enforcement strategies, helmet disadvantages (discomfort, visual/auditory blockage, and thermal dysregulation), risky behaviors (riding while drunk or high on drugs), sex and/or age factors, and the location and time of the injury event (rural vs. urban locations, day vs. night riding). From the perspective of policymakers, the findings of this review are of utmost importance and could be used in addressing the challenge of inadequate compliance with helmet use.